2020
DOI: 10.3389/fpls.2020.603687
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature and Elevated Carbon Dioxide Modify Berry Composition of Different Clones of Grapevine (Vitis vinifera L.) cv. Tempranillo

Abstract: Tempranillo is a grapevine (Vitis vinifera L.) variety extensively used for world wine production which is expected to be affected by environmental parameters modified by ongoing global climate changes, i.e., increases in average air temperature and rise of atmospheric CO2 levels. Apart from determining their effects on grape development and biochemical characteristics, this paper considers the intravarietal diversity of the cultivar Tempranillo as a tool to develop future adaptive strategies to face the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 83 publications
4
57
0
Order By: Relevance
“…Moreover, field data on the impact of increased atmospheric CO 2 concentration on berry metabolism are scarce and need to be further investigated, in particular in combination with different abiotic stresses such as increased temperature and drought. Though difficult to conduct in field conditions and so far only carried out on fruiting cuttings (Salazar-Parra et al, 2012 ; Kizildeniz et al, 2015 ; Martinez-Luscher et al, 2015 ; Arrizabalaga-Arriazu et al, 2020a , b ) such multi-stress experiments will improve understanding of how climate change will impact vine and berry physiology, and will help develop mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, field data on the impact of increased atmospheric CO 2 concentration on berry metabolism are scarce and need to be further investigated, in particular in combination with different abiotic stresses such as increased temperature and drought. Though difficult to conduct in field conditions and so far only carried out on fruiting cuttings (Salazar-Parra et al, 2012 ; Kizildeniz et al, 2015 ; Martinez-Luscher et al, 2015 ; Arrizabalaga-Arriazu et al, 2020a , b ) such multi-stress experiments will improve understanding of how climate change will impact vine and berry physiology, and will help develop mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In multistress experiments with Temperanillo fruiting cuttings where future temperature (+4°C) and CO 2 (700 ppm) conditions where simulated, high CO 2 in particular when combined with high temperature hastened berry ripening, sugar accumulation, malic acid respiration and reduced the aforementioned high temperature induced anthocyanin–sugar decoupling (Arrizabalaga-Arriazu et al, 2020a ).…”
Section: Co 2 Concentrationmentioning
confidence: 99%
“…A growing body of evidence shows that grapevine phenology is hastened by elevated temperatures [ 12 , 13 , 38 ] and high atmospheric CO 2 concentration [ 13 , 39 ]. Warmer temperature joint to elevated CO 2 concentrations also produced, in general, a faster grapevine development but the effect had different intensity depending on the commercial clone tested [ 39 , 40 , 41 ]. By contrast, in our study, the ECET treatment did not modify the length of phenological phases in the genotypes from old varieties tested being.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it was reported that high temperatures produced malate losses in commercial varieties as Shiraz [ 15 ], Cabernet Sauvignon, Chardonnay [ 14 ], and Tempranillo [ 29 ]. In addition, studies in which the elevated CO 2 was combined with high temperature have reported decreases of malic acid in different commercial clones of Tempranillo [ 39 , 41 ]. Our results partially agree with those described in commercial varieties because some old genotypes (TEMP, TV, and GRA63) also experienced significant decreases of titratable acidity in response to ECET treatment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Last, but not least, to the best of our knowledge, all transcriptomic studies published so far on grapevine deal with the response to one single abiotic factor, often applied in controlled or semi-controlled conditions. This is in contradiction with the fact that in the frame of the ongoing global climate change, several abiotic factors will be affected and will most certainly interact to affect grapevine physiology and grape ripening, as evidenced for UV-B and drought ( Martinez-Lüscher et al, 2014 ; Martinez-Luscher et al, 2015a ), water availability and elevated temperature ( Zarrouk et al, 2016 ), UV-B, temperature and ambient CO 2 levels ( Martinez-Luscher et al, 2015b ; Martinez-Lüscher et al, 2016 ; Arrizabalaga-Arriazu et al, 2020 ). Future transcriptomic studies aiming to provide relevant molecular data to breed new cultivars better adapted to future climatic conditions will have to integrate stress combinations in their experimental design.…”
Section: Molecular Tools For Understanding the Response Of Grapevinementioning
confidence: 96%